One Government One Voice? Government Narrative in Crisis Communication during the Pandemic - Rahmanto, Andre Noevi (Universitas Semarang, 2023)
Introduction: Government public relations ideally conveys policies and regulations in an integrated manner (one government one voice), but in reality there is often different and contradictory information in each government institution, thus confusing the public and hindering the handling of the pandemic. This research answers the question of how the crisis narrative is built by 5 (five) central government institutions in Indonesia through their official websites, whether the narrative tends to be integrated or vice versa. Methods: The method used in this study is qualitative content analysis where the author collects all news materials on 5 (five) official websites of government agencies, namely: the Covid-19 Task Force, the Ministry of Information and Communication, the Ministry of Health, the Cabinet Secretariat and the State Secretariat, in March-August 2020. Findings: Data were analyzed based on the principles of Crisis and Emergency Risk Communication (CERC) as a reference for coherence (integration) of narratives between institutions. The results of the study indicate that CERC principles are used comprehensively by the five institutions studied. In general, the narratives built by the five institutions tend to be integrated on the issues: (1) the narrative of the initial responding; (2) the narrative of handling and controlling; (3) the narrative of helping and caring; (4) the narrative of regulating and advising. Originality: The study has novelty in the application of crisis communication based on the CERC principles of the Covid-19 pandemic which is viewed comparatively in the narratives of 5 (five) Indonesian government institutions.